A Facile Synthesis of Green-Blue Carbon Dots from Artocarpus lakoocha Seeds and Their Application for the Detection of Iron (III) in Biological Fluids and Cellular Imaging - Yadav P.K.; Singh V.K.; Kumar C.; Chandra S.; Jit S.; Singh S.K.; Talat M.; Hasan S.H. (My University, 2025)
Herein, a facile, green and eco-friendly approach has been applied for the synthesis of fluorescent green-blue carbon dots (GB-CDs) through the one-pot hydrothermal treatment of Artocarpus lakoocha seeds for the first time and entirely characterized via a variety of instrumental techniques like fluorescent spectroscopy, Transmission Electron Microscopy (TEM), X-Ray Photoelectron Spectra (XPS), X-Ray diffraction (XRD) and Fourier Transform Infra-red (FTIR) analysis. The as-prepared GB-CDs displayed high fluorescent quantum yield (QY) up to 38.5% and high photostability based on which GB-CDs were successfully applied as a sensitive nanoprobe for the detection of Fe3+ ion. The sensing of Fe3+ shows a linear range from 2 to 6 μM and the limit of detection was found to be 0.62 μM. The sensing of Fe3+ was further investigated in the bona fide sample like river water and human blood serum. In addition, to explore the potential application, MTT assay was carried out on SH-SY5Y neuroblastoma cells. The results showed negligible cytotoxicity as well as high cell viability, which revealed that GB-CDs could be utilized as a fluorescent probe in living cells. © 2019 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim